THE EFFECT OF PROJECT-BASED LEARNING ON EARLY NUMERACY SKILLS OF CHILDREN AGED 5–6 YEARS AT TK TA MUSLIMAT NU 12 NOLOKERTO, KALIWUNGU DISTRICT, KENDAL REGENCY - Dalila (BELIA Early Childhood Education Papers, 2026)
This study aimed to determine the effect of Project-Based Learning (PjBL) on the early numeracy skills of children aged 5–6 years at TK TA Muslimat NU 12 Nolokerto. The study employed a quantitative approach with a pre-experimental one-group pretest–posttest design. The participants consisted of 59 children. Data were collected through observation, questionnaires, and documentation, and analyzed using a Paired Samples t-test. The results showed a significant difference between pretest and posttest scores (Sig. = 0.000 < 0.05; t = 8.405), indicating that Project-Based Learning significantly improved children's early numeracy skills.